2022
DOI: 10.1111/iej.13785
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes reporting in systematic reviews on vital pulp treatment: A scoping review for the development of a core outcome set

Abstract: Background: A large number of research reports on vital pulp treatment (VPT) has been published over the last two decades. However, heterogeneity in reporting outcomes of VPT is a significant challenge for evidence synthesis and clinical decision-making. Objectives:To identify outcomes assessed in VPT studies and to evaluate how and when outcomes are measured. A subsidiary aim was to assess evidence for selective reporting bias in the included studies. The results of this review will be used to inform the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
0
20
1
Order By: Relevance
“…How to cite this article: El-Karim, I., Duncan, H.F., Nagendrababu, V. & Clarke, M. (2022) The importance of establishing a core outcome set for endodontic clinical trials and outcomes studies. International Endodontic Journal, 00, 1-7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How to cite this article: El-Karim, I., Duncan, H.F., Nagendrababu, V. & Clarke, M. (2022) The importance of establishing a core outcome set for endodontic clinical trials and outcomes studies. International Endodontic Journal, 00, 1-7.…”
Section: Discussionmentioning
confidence: 99%
“…In endodontics, CROs are interpretation of data obtained from detailed history taking together with clinical and/or radiographic examination. CROs such as a history of pain and heightened, painful response to percussion/ palpation are crucial outcomes that have been used in recent endodontic treatment outcomes studies (Cushley et al, 2022;Shah et al, 2022). However, the measures used for CROs are often not standardized or validated.…”
Section: Clinician-reported Outcomesmentioning
confidence: 99%
“…The primary goal of pulp therapy is to maintain the integrity and health of the teeth and their supporting tissues while maintaining the vitality of the pulp [ 1 ]. The prognosis of teeth that underwent vital pulp therapy (VPT) procedures is evaluated on the basis of clinical symptoms, percussion, radiographic examination, and pulp testing [ 2 ]. Diagnostic pulp tests are, therefore, an essential aid in determining the outcome of various pulp-capping procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the systematic review process is to identify outcomes reported in all clinical studies in humans in order to generate list of outcomes that are to be categorized according to health intervention taxonomy (Dodd et al, 2018) for validation via a subsequent Delphi process and consensus meeting. The process has been completed for VPT (Cushley et al, 2022), surgical endodontics (Shah et al, 2022) and non-surgical root Conclusions: Several important outcomes including survival, root development, tooth discolouration and periapical healing have been identified in this review which could inform the development of a COS in this area.…”
Section: Introductionmentioning
confidence: 99%